Barriers to using cloud computing in sustainable construction in Nigeria : A fuzzy synthetic evaluation - Omer, Mazen M.; Kineber, Ahmed Farouk; Oke, Ayodeji Emmanuel; Kingsley, Chukwuma; Alyanbaawi, Ashraf; Rached, Ehab Farouk; Elmansoury, Ali (MDPI, 2023)
This study aims to assess the barriers impeding cloud computing (CC) applicability in sustainable construction. A total of 11 barriers in the use of CC were identified for the literature review. A questionnaire survey was used to collect the data from construction stakeholders. In total, 101 valid responses were obtained and analyzed using mean ranking, normalized value (NV), overlapping analysis, Kruskal–Wallis H test, exploratory factor analysis (EFA), and fuzzy synthetic evaluation (FSE). The EFA extracted four interrelated components: social, economic, expertise, and connectivity. These components were exported for mathematical analyzing using the FSE technique. As a result, the FSE indicated that connectivity is the highest-impacted component, while the overall impact level of barriers is inclined to high regarding CC applicability in sustainable construction. This is due to other components having an average to high impact level. In this regard, the findings reflect the actual current status of developing countries in using CC in sustainable construction. These research findings will allow construction stakeholders to take proactive steps toward increasing the use of CC in their current and future sustainable construction. Decision-makers could also make accurate decisions that are well-informed in managing CC barriers. This paper provides stakeholders, researchers, and decision-makers with a list of CC barriers that hinder developing countries.